GUI design for Android apps - Wang, Tao (Expert's voice in app development., 2014)
Through tutorials, code samples, and case studies, this book shows the principles for user-interface design for Android apps running on the Intel platform, including smartphones, tablets and embedded devices. It is jointly developed for individual learning by Intel Software College and China Shanghai JiaoTong University, and is excerpted from Android Application Development for the Intel Platform. Coverage includes: key aspects of why UI and UX design for embedded systems is different than for desktops; troubleshooting UI design issues; understanding how key concepts such as state transition, context class, and intent work; how to use the interface app design tools provided by Android; planning for complex apps (apps with multiple activities); and optimizing app design for touch screen input. This book is primarily for app developers, software engineers and open-source programming enthusiasts, but can also be used by for training programs and Codeacademy-style programs. --